2022
DOI: 10.1080/10717544.2022.2160518
|View full text |Cite
|
Sign up to set email alerts
|

Targeted drug delivery strategy: a bridge to the therapy of diabetic kidney disease

Abstract: Diabetic kidney disease (DKD) is the main complication in diabetes mellitus (DM) and the main cause of end-stage kidney disease worldwide. However, sodium glucose cotransporter 2 (SGLT2) inhibition, glucagon-like peptide-1 (GLP-1) receptor agonist, mineralocorticoid receptor antagonists and endothelin receptor A inhibition have yielded promising effects in DKD, a great part of patients inevitably continue to progress to uremia. Newly effective therapeutic options are urgently needed to postpone DKD progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 137 publications
(126 reference statements)
0
6
0
Order By: Relevance
“…Recent studies revealed the beneficial effects of chitosan nanoparticles and COS in ulcerative colitis, autoimmune encephalitis, autoimmune arthritis, lupus nephritis, and autoimmune hepatitis [32][33][34]; however, there have been a limited number of studies about COS in renal diseases. Chitosan nanoparticle-encapsulated drugs combined with metformin reduced creatinine, proteinuria, and downregulated TNF-α, IL-6, and IL-1β in type 2 DM rats [35,36]. Zhang H., et al, revealed that COS ameliorated proteinuria and the expression of kidney injury markers and may reverse pathologic change in diabetic rats' kidneys [37].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed the beneficial effects of chitosan nanoparticles and COS in ulcerative colitis, autoimmune encephalitis, autoimmune arthritis, lupus nephritis, and autoimmune hepatitis [32][33][34]; however, there have been a limited number of studies about COS in renal diseases. Chitosan nanoparticle-encapsulated drugs combined with metformin reduced creatinine, proteinuria, and downregulated TNF-α, IL-6, and IL-1β in type 2 DM rats [35,36]. Zhang H., et al, revealed that COS ameliorated proteinuria and the expression of kidney injury markers and may reverse pathologic change in diabetic rats' kidneys [37].…”
Section: Discussionmentioning
confidence: 99%
“…Although these drugs have shown encouraging efficacy in treating DKD proteinuria, some patients continue to experience uremia. Increasing evidence has shown that targeted drug delivery strategies, such as macromolecular carriers, nanoparticles, and liposomes, can improve drug efficacy and reduce adverse side effects, which may become a new milestone in treating DKD [130]. HDAC4 is involved in podocyte injury in DKD, and HDAC4 siRNA shows good therapeutic prospects for DKD.…”
Section: Targeted Precision Therapymentioning
confidence: 99%
“…Diabetic nephropathy (DN) is a prevalent microvascular complication of diabetes and the leading cause of end-stage renal disease (ESRD) in developed countries and developed regions of China (Ma, 2018 ; Johansen et al, 2021 ). Approximately 40% of DM patients will eventually develop DN (Chen et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%